Quality management implementation in higher education practices, models, and case studies - Sony, Michael, d 1981- e editor; Karingada, Kochu Therisa, d 1983- e editor; Baporikar, Neeta (Advances in Higher Education and Professional Development (AHEPD) Book Series, 2020)
"This book examines the implementation of quality management systems in research, teaching, learning, administrative processes, and other facets of higher education"--